2012
DOI: 10.21608/ejabf.2012.2108
|View full text |Cite
|
Sign up to set email alerts
|

Effect of spawning month, dietary protein and pond protection on fry production of the Nile tilapia, Oreochromis niloticus

Abstract: The practical work of the present experiments was carried out at the World Fish Center, Abbassa, Abou Hammad, Sharkia, Egypt. The experiment aimed to investigate the effect of spawning month (April and May), dietary protein level (25 or 35%) and protection of spawning tanks (covering or uncovering of the spawning tanks) on fry production and average fry weight of the Nile tilapia. The obtained results can be summarized as follow:-Fry production/tank were found to be 6462 and 19082/tank during the two months Ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 12 publications
1
1
0
Order By: Relevance
“…Gonad weight was highly correlated with GSI in both males and females (0.96 and 0.97, respectively). These results are in agreement with Sultan et al (2011) who reported significant and positive correlation coefficients between tilapia body length and ovary weight (0.51); body length and GSI (0.39); body weight and ovary weight (0.61); body weight and GSI (0.42). The current results indicate that whenever males and females body weight or length increase, the gonads weight and GSI will be also increased.…”
Section: Descriptive Statistics and Coefficients Of Correlationsupporting
confidence: 92%
“…Gonad weight was highly correlated with GSI in both males and females (0.96 and 0.97, respectively). These results are in agreement with Sultan et al (2011) who reported significant and positive correlation coefficients between tilapia body length and ovary weight (0.51); body length and GSI (0.39); body weight and ovary weight (0.61); body weight and GSI (0.42). The current results indicate that whenever males and females body weight or length increase, the gonads weight and GSI will be also increased.…”
Section: Descriptive Statistics and Coefficients Of Correlationsupporting
confidence: 92%
“…This indicated that, the fry number produced per fish for diet contained 600 mg L-carnitine/kg diet was better than those of other treatments. Soltan et al, (2012) reported that, Dietary protein and L-carnitine has been found to influence seed production in tilapia. An increase in egg production with an increase in L-carnitine levels has been reported for Nile tilapia, O. niloticus (Santiago, et al, 1985) and Taiwanese red tilapia (Chang et al, 1988).…”
Section: Reproductive Performance For O Niloticus Femalesmentioning
confidence: 99%